Prevalence of chronic kidney disease and its risk factors among Type 2 diabetes patients in a tertiary care hospital - Noor Mohamed Rasik B; Sakthi Suganya ST; Vikram Manamala Sudhakar; Vignesh C (Asian Journal of Medical Sciences, 2024)
Background: An increased chance of developing chronic kidney disease (CKD), which has higher morbidity and mortality, exists among patients with Type 2 diabetes (T2D). Aims and Objectives: Our goal was to determine and classify the anthropometric, physiological, and demographic risk factors for CKD in individuals with T2D. Materials and Methods: A cross-sectional research study was conducted at a tertiary care hospital involving 218 participants. Data were collected on various parameters including age, gender, education level, employment status, height, weight, blood pressure, hemoglobin levels, and estimated glomerular filtration rates (eGFRs). Participants were selected based on specific inclusion and exclusion criteria, and rigorous statistical analyses were applied to the collected data. Using the SPSS program, we analyzed the data, and when the P<0.05, we declared the results statistically significant. Results: There were 218 people in the research, 58.3% of whom were male and 41.7% of whom were female. The mean age group was between 51 and 60 at 36.2%. The age group distribution among the patients showed significant value (P<0.0001). About 87.6% of the patients had normal weight. 49.5% were recorded in Stage 1 CKD. Fasting blood sugar has a negative correlation (−182) with glomerular filtration rate (GFR) and shows a significant result. The post-prandial blood sugar value is also statistically significant and negatively relates to GFR. In addition, random blood sugar and glycated hemoglobin also reported statistically significant values. Conclusion: In individuals with T2D, it was determined that significant risk factors for the onset of CKD include eGFR, age, and the duration of diabetes. Males had a considerably greater incidence of CAD, peripheral neuropathy, and diabetic foot.